Effect of nitrogen and transplanting date on yield and yield components of aromatic rice - Islam, MS; Hossain, MA; Chowdhury, MAH; Hannan, MA (Journal of the Bangladesh Agricultural University, 2010)
A field experiment was conducted to find out the effect of nitrogen levels and transplanting dates on the yield and yield components of aromatic rice cv. Kalizira. The experiment was laid out in a randomized complete block design with three replications using four( 0, 50, 100, and 150 kg N ha-1 ) levels of nitrogen and three transplanting dates (10 August, 22 August and 04 September, 2007 ) along with the basal doses of triple super phosphate (TSP), muriate of potash (MoP) and gypsum. The study revealed that most of the yield and yield contributing characters with few exceptions were significantly influenced by nitrogen levels and transplanting dates. They had significant positive effect on tillers hill-1, tillers hill-1, grains panicle-1 and straw yield. The highest grain yield (2.63 t ha-1) was observed in 100 kg N ha-1 with 10 August transplanting treatment and straw yield (6.43 t ha-1) was found highest in 150 kg N ha-1 with same date of transplanting and the lowest grain (1.83 t ha-1) and straw yields (5.14 t ha-1) were found in N control treatment with transplanting date of 04 September. The highest grain length (4.68 mm), grain breadth (2.49 mm) and imbibition ratio (6.93) were observed with 100 kg ha-1 N rate coupled with 10 August transplanting, and for length-breadth ratio, the same rate recorded the highest result, but with different transplanting date i.e. 22 August. Keywords: Aromatic rice; Kalizira; Nitrogen; Transplanting date DOI: 10.3329/jbau.v6i2.4824 J. Bangladesh Agril. Univ. 6(2): 291-296, 2008